W świecie brzmień, Sienkiewiczowskich postaci i wartości (arcydzieł): z Profesorem Andrzejem Stoffem rozmawia Beata Garlej - Garlej , Beata (Przestrzenie Teorii, 2022)
This is a transcript of a conversation with Andrzej Stoff, for whom Roman Witold Ingarden’s philosophical thought on art and literature is a source of inspiration for his research. The interview presents a few issues representative of the analyses of the Toruń-based scholar, arising from Ingarden’s theory of literary work, which for the interlocutor turns out to be an “open” theory, also encouraging today’s literary scholars and literary theorists to continue and deepen the assumptions adopted by Stoff when considering the problems of the ontology and axiology of a literary work.